Creating Interest in Learners - Matt Benge; Amy Harder (EDIS)
AEC-393, a 3-page illustrated fact sheet by Matt Benge and Amy Harder, describes the “Interest Approach” to classroom instruction, methods for creating interest, and natural impulses that may be appealed to in teaching to help create interest. Includes references. Published by the UF Department of Agricultural Education and Communication, September 2008.